Productivity improvement by means of method engineering tools and automation in ice cream production at bonanza company - Menendez Elguera, Edgar Walter (2023)
The production of ice cream has become very popular in the last decade, showing a gradual increase in food consumption preference, generating millions of dollars in the international market, becoming a sector with great technological progress helping to improve the ice cream industry. Even so, there are companies that carry out the processes in an artisanal manner or with little technological modernization, as in the case of Bonanza. The objective of this article is to improve productivity through the use of method engineering tools and industrial automation in the production of the ice cream line of the Bonanza company. In a guided inspection, the operations diagram, process analysis and route diagram were determined. Finding dead times, bottlenecks, congestion and misuse of resources. With the help of Autodesk Inventor, Labview and TinkerCAD programs, the design and simulation of automated machines for the process of cleaning, inspection and weighing of fruit was carried out. This allowed to go from 30 min, 41 min and 65 min to 14 min and 20 minutes by merging the last two processes respectively. In addition to improving all internal processes and restructuring the path of the route. In conclusion, with the implementation of this project, the product execution time was reduced by 3 hours, optimal resources and increased productivity in the Bonanza company.